2020
DOI: 10.33824/pjpr.2020.35.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Research Self-Efficacy Among Students: Role of Metacognitive Awareness of Reading Strategies, Research Anxiety, and Attitude Towards Research

Abstract: The present study aimed to explore the role of metacognitive awareness of reading strategies, research anxiety, and attitude towards research in research self-efficacy among students at university currently conducting research as part of their degree requirement. The role of perceived supervisor’s satisfaction from research and intensity of reading as moderators was also analyzed. Research Self-Efficacy Scale (Rezaei & Zamani-Miandashti, 2013), Metacognitive Awareness of Reading Strategies (Mokhtar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Another is the study by Özer (2021) which revealed that a moderately strong association is found between URL: www.onlinesciencepublishing.com | February, 2023 emotional intelligence and grit. Also somewhat in agreement with the outcome of this study are findings on the influence of non-cognitive factors like attitude, attitude towards research, achievement scores time management skills, research self-efficacy, professional experience and educational preparations, supervisor's dissatisfaction, metacognitive awareness of reading strategies and research self-efficacy, on research anxiety (Akcoltekin, 2015;Ashrafi-Rizi et al, 2014;Butt & Shams, 2013;Maschi et al, 2013;Merç, 2016;Obaseki & Agu, 2019;Razavi et al, 2017;Rezaei & Zamani-Miandashti, 2013;Saracaloğlu, 2008;Wajid & Jami, 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…Another is the study by Özer (2021) which revealed that a moderately strong association is found between URL: www.onlinesciencepublishing.com | February, 2023 emotional intelligence and grit. Also somewhat in agreement with the outcome of this study are findings on the influence of non-cognitive factors like attitude, attitude towards research, achievement scores time management skills, research self-efficacy, professional experience and educational preparations, supervisor's dissatisfaction, metacognitive awareness of reading strategies and research self-efficacy, on research anxiety (Akcoltekin, 2015;Ashrafi-Rizi et al, 2014;Butt & Shams, 2013;Maschi et al, 2013;Merç, 2016;Obaseki & Agu, 2019;Razavi et al, 2017;Rezaei & Zamani-Miandashti, 2013;Saracaloğlu, 2008;Wajid & Jami, 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 96%
“…Only recently has it been discovered that enormous number of learners and some faculty members experience research anxiety within the tertiary education system according to research (Ashrafi-Rizi et al, 2014;Bayar, Bayar, Eğmir, Ödemiş, & Kayir, 2013;Einbinder, 2014;Merç, 2016;Onwuegbuzie, 1997;Rezaei & Zamani-Miandashti, 2013;Saracaloğlu, 2008;Wajid & Jami, 2020). As such the concept of research anxiety is only beginning to take relevance in undergraduate and post graduate research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When metacognitive awareness is a mediator in the mediation model, problem-solving abilities still showed a positive, significant influence on mathematics achievement. This reduction showed that metacognitive awareness moderated the association between problem-solving skills and mathematics success in secondary school students (Wajid & Jami, 2020). According to Wajid and Jami (2020), problemsolving and metacognition are complicated cognitive skills that have obtained little attention.…”
Section: Metacognitive Awareness Mediator Role In Mathematicsmentioning
confidence: 99%
“…This reduction showed that metacognitive awareness moderated the association between problem-solving skills and mathematics success in secondary school students (Wajid & Jami, 2020). According to Wajid and Jami (2020), problemsolving and metacognition are complicated cognitive skills that have obtained little attention. Wajid and Jami (2020) mention that metacognitive awareness processes vary depending on the cognitive task.…”
Section: Metacognitive Awareness Mediator Role In Mathematicsmentioning
confidence: 99%